Profiling e-Science infrastructures with kernel and application benchmarks. (1st January 2014) - Clematis, Andrea; D'Agostino, Daniele; Galizia, Antonella; Quarati, Alfonso
Resources benchmarking is a promising though challenging opportunity for research communities to better exploit e-Science infrastructures. The paper investigates the suitability of an integrated two-level benchmarking approach in supporting resources ranking on a performance basis. The coupling of different benchmarking techniques (i.e. kernel and application benchmarks) is intended to grasp the behaviour of computational environments also with respect to real workloads so as to address a more suitable and efficient assignment of resources to the applications submitted by users. To confirm the appropriateness of our approach, an experimentation on a test bed was carried out which highlighted significant differences amongst the performance figures of the two levels of benchmarks. Some useful rules of thumb emerged from our experimentation that could be taken into account to fruitfully adopt this double-space approach to similar scenarios of use.